Cover Image. (18th December 2018) - Woodward, Michael; Arthur, Antony; Darlington, Nicole; Buckner, Stefanie; Killett, Anne; Thurman, John; Buswell, Marina; Lafortune, Louise; Mathie, Elspeth; Mayrhofer, Andrea; Goodman, Claire
Abstract : The cover image is based on the Research Article The place for dementia‐friendly communities in England and its relationship with epidemiological need, by Michael Woodward et al., https://doi.org/10.1002/gps.4987 .